(3cJGH GdGYJbGO hGdgOGjI Edi SHjd GdQTGOs - (3CHh HcQ CMeO Hf GdMSjf Hf Ydj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s ((3HOQ GdOjf CMeO GdHQGbi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdNdb eG TGA eG TGA CeG HYO aGfi HJhajb Gddg SHMGfg hJYGdi UfaJ ajeG jaJbQ Edi GdJcdja Edi eYQaI GUhd GdYde haQhYg eG bO GfJTQ HGH Chd eG jLH Ydi GdYHO eYQaJg hGdGbQGQ Hg s
(3BNQgG (B:s
(3jfJgi HHGH GSJNdGa CHj GdMSf Ydi Hf CHj WGdH Hf YHO GdeWdH Hf gGTe QVi Gddg Yfg s
(3gPg gi GdfSNI GdhMjOI GdJi jPcQgG HQhcdeGf hai ecJHI fOhI GdYdeGA Hdcfghs
(3fSNI eSfI HNW MOjK GjVkG hdYd gPg efbhdg YfgGs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
Keywords: (3GdJhMjO hGdedd hGdfMds